Women and Children First… Why Not Build Enough Lifeboats? - Maxwell, Gary J. (Columbia Journal of Gender and Law, 2000)
For nearly a year, a multi-disciplinary team of professionals designed and sponsored a conference intended to develop a stronger and more effective working relationship between women’s rights advocates in the domestic violence context and child protective advocates. Conference presenters included Victor La Cerva, M.D., Medical Director for the New Mexico Department of Health’s Family Health Bureau, and Linda Spears, Director of Child Protective Services for the Child Welfare League of America. I was asked to design case scenarios (See Appendix, p. 47) which were reviewed and discussed by a panel of professionals, including representatives of law enforcement, the courts, child protective services, women’s shelters, and individuals playing the roles of mom, dad, and child. The conference closed with individual community groups working on designing a plan for their community whereby women’s rights and child protection advocates could work together.